Pengaruh Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Karyawan pada CV Mitra Tani Farm - Wanda Hamida; Syahrum Agung; Hannisa Rahmaniar Hasnin (CV. ITTC INDONESIA, 2024)
Employee performance at the company is not fully optimal due to the lack of work motivation and work discipline at CV Mitra Tani Farm. This research aims to determine the effect of work motivation and work discipline on employee performance, with a total population and sample taken of 48 respondents at CV Mitra Tani Farm. The method used is research instruments such as statements distributed to employees which are processed using the SPSS version 26 application. Work motivation and work discipline variables on employee performance using multiple regression analysis methods, normality tests, multicollinearity tests, heteroscedasticity tests, t tests, f tests and coefficients. determination. The results of this research show that the work motivation variable has a positive and significant effect on employee performance, the work discipline variable has a positive and significant effect on employee performance and the work motivation and work discipline variables simultaneously have an effect on employeeperformance at CV Mitra Tani Farm.